Комплаєнс як інструмент управління маркетинговими комунікаціями українських брендів - Марченко, О.М.; Леськів, Г.З.; Пушак, Я.Я. (Управління економікою: теорія та практика, 2025)
У статті узагальнено наукові й нормативні підходи до трактування поняття «комплаєнс» та обґрунтовано доцільність його розгляду як інтегрованого управлінського процесу, спрямованого на забезпечення відповідності діяльності організації правовим, етичним і соціальним нормам. Визначено специфіку комплаєнсу у сфері маркетингових комунікацій та окреслено ключові напрями комплаєнс-ризиків, пов’язаних із рекламною діяльністю, цифровими каналами комунікації та соціально чутливим контентом в умовах війни. Доведено, що формально правомірні комунікації можуть спричиняти репутаційні втрати за ігнорування соціально-етичного контексту. Запропоновано механізми інтеграції комплаєнсу в управління маркетинговими комунікаціями з метою мінімізації ризиків і збереження довіри до брендів. In the context of increasing regulatory pressure, growing reputational risks, and heightened public sensitivity to business activities, compliance has become a key instrument of organizational management. This issue is particularly relevant for marketing communications, which not only serve as a tool for brand promotion but also significantly influence public trust and corporate reputation, especially under conditions of social instability. The article provides a synthesis of scientific and regulatory approaches to the interpretation of the concept of compliance and substantiates the expediency of considering compliance as an integrated management process. This process combines activities aimed at ensuring compliance, organizational capacity to maintain it, orientation toward fulfilling obligations, and the ability to adapt organizational behavior to relevant legal, ethical, and social norms. The specificity of compliance in the field of marketing communications is identified, and the main areas of compliance risks related to advertising activities, the use of digital communication channels, value-based content, and cooperation with external communication partners are outlined. The analysis of contemporary practices demonstrates that even formally lawful marketing communications may lead to significant reputational losses if the social and ethical context is not adequately taken into account. The article proposes key mechanisms for implementing compliance in the management of marketing communications, including institutional allocation of compliance responsibilities, integration of compliance procedures into content development processes, systematic monitoring of the communication environment, and the formation of a corporate culture of responsible communication. The practical value of the study lies in the possibility of applying the proposed approaches to minimize compliance risks, enhance trust among stakeholders, and ensure the sustainable development of organizations.